HUBUNGAN VAKSINASI DENGAN HOSPITALISASI COVID-19 DI DKI JAKARTA - Kristin Mutiara Tarigan (2023)
An viral disease that affects the respiratory system is COVID-19. Hospitalization status refers to COVID-19 cases who experience hospitalization or isoman. The level of COVID-19 vaccination in DKI Jakarta is still considered low. The purpose of this study is to ascertain the association between COVID-19 hospitalization and immunization. The DKI Jakarta Provincial Health Office provided secondary data for this cross sectional quantitative investigation. The participants in this study were DKI Jakarta citizens who were over 6 years old. The sample used in this study is. Vaccination status, gender, and age were found to be associated with COVID-19 hospitalization in DKI Jakarta based on bivariate data. According to the multivariate findings, elderly age is the main contributing factor to COVID-19 hospitalization in DKI Jakarta. Compared to minors, respondents who are older than 60 years have an 85,939 times higher chance of being hospitalized for COVID-19 in DKI Jakarta. There is a relationship between age and immunization history.